A concise approach for building the s−T diagram for Mn–Fe–P–Si hysteretic magnetocaloric material. (16th August 2017) - Christiaanse, T V; Campbell, O; Trevizoli, P V; Misra, S; van Asten, D; Zhang, L; Govindappa, P; Niknia, I; Teyber, R; Rowe, A
Abstract: The use of first order magnetocaloric materials (FOM's) in magnetic cycles is of interest for the development of efficient magnetic heat pumps. FOM's present promising magnetocaloric properties; however, hysteresis reduces the reversible adiabatic temperature change ( Δ T a d ) of these materials, and consequently, impacts performance. The present paper evaluates the reversible Δ T a d in a FOM. Six samples of the Mn–Fe–P–Si material with different transition temperatures are examined. The samples are measured for heat capacity, magnetization, and adiabatic temperature change using heating and cooling protocols to characterize hysteresis. After correcting demagnetizing fields, the entropy-temperature ( s − T ) diagrams are constructed and used to calculate adiabatic temperature change using four different thermal paths. The post-calculated Δ T a d is compared with experimental data from direct Δ T a d measurements. Most of the samples of Mn–Fe–P–Si show that post-calculated Δ T a d resulting from the heating zero field and cooling in-field entropy curves align best with the Δ T a d measurements. The impact of the demagnetizing field is shown in terms of absolute variation to the post-calculated Δ T a d . A functional representation is used to explain observed data sensitivities in the post-calculated Δ T a d .